Influenza vaccine effectiveness in children: a retrospective study on eight post-pandemic seasons with trivalent inactivated vaccine - Colucci, Maria Eugenia; Affanni, Paola; Cantarelli, Angelo; Caruso, Luca; Bracchi, Maria Teresa; Capobianco, Emanuela; Zoni, Roberta; Paini, Giulia; Odone, Anna; Mohieldin Mahgoub Ibrahim, Mostafa Mohieldin; Veronesi, Licia (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The global burden of disease attributable to seasonal influenza virus in children is difficult to quantify. Children with chronic medical conditions and healthy children may experience severe or fatal complications. Aim of the study was to estimate the influenza vaccine effectiveness (VE) in a cohort of outpatient children. Methods: From 2010 to 2018, a Pediatrician of Parma from the InfluNet network of Emilia-Romagna Region, performed nasal/throat swabs on every child with Influenza-like illness at least 14 days from the vaccination with trivalent vaccine. VE estimates against influenza season, virus type and subtype and age group were evaluated using a test-negative design. Results: 2,480 swabs were performed. The 57.6% of the analyzed swabs were positive for influenza viruses. Type A (57%) and type B viruses (43%) co-circulated. The 37.1% of type A viruses belonged to subtype A(H3N2), 19.4% to subtype A(H1N1)pdm09. The subtype A(H3N2) was prevalent among children up to 23 months (42.4%) while the type B in the 2-4 (40.7%) and 5-16 year old age groups (49.4%). Overall, 19.9% of the children were vaccinated. The highest prevalence of vaccinated subjects was found in children aged 5-16 (30.5%). The VE against subtype A(H1N1)pdm09 was 63% (95%CI 42.6-76.0), against type B 27.5% (95%CI 7.9-42.9) and against subtype A(H3N2) -14.3% (95%CI - 46.0-10.7). Conclusions: Our findings represent a useful contribution to the ongoing debate about the appropriateness of including influenza vaccination for healthy children, 6 months and older, in the updating National Vaccine Prevention Plan (PNPV).